Impact of Saccharomyces Cerevisiae and/or Its Cell Wall Supplementation in Dairy Cow Diet on Passive Immunity Transfer in their Calves - Beldjouhar, Nadjiba; AYAD, mohamed amine; saim, Said mohamed; AYAD, Issam; derrer, sofiane; Smadi, Mustapha Adnane; saidj, dahia (Archives of Veterinary Science, 2025)
Abstract: Early detection of failed transfer of passive immunity (FTPI) is crucial to prevent neonatal diseases and mortality. This study evaluates the effect of supplementing dairy cows with Saccharomyces Cerevisiae and/or a yeast wall during the last month of pregnancy on the transfer of passive immunity to calves. Forty-five Montbeliarde dairy cows were divided into four groups: a control group (CON; n=13) with no supplementation, an SC group (n=12) receiving 5 g/day of S. Cerevisiae yeast, a YW group (n=10) receiving 5 g/day of yeast wall (20% mannans, 20% β-glucans), and an SCYW group (n=10) receiving a combination of 5 g SC and 5 g YW. At calving, colostrum and blood samples were collected to measure calf serum IgG concentration using radial immunodiffusion (RID) and compare results with the %Brix refractometer. A one-way ANOVA assessed the effects of supplementation type, colostrum quality, and calf sex. A Spearman correlation test evaluated the %Brix refractometer as an indirect tool for IgG estimation. Results showed a significant improvement in passive immunity transfer with supplementation (P<0.001), particularly in the SC and SCYW groups (P<0.01). Colostrum quality had a significant effect, whereas calf sex had no impact. A positive correlation (r=0.536) was observed between RID and %Brix. In conclusion, supplementing dairy cows with yeast during the last month of pregnancy enhances passive immunity transfer. The %Brix refractometer is a viable alternative to RID for estimating serum IgG concentration and detecting FTPI cases. Keywords: Dairy cows; Supplementation; FTPI; Immunoglobulin; RID.